Malignant phyllodes tumor in the right breast and invasive lobular carcinoma within fibroadenoma in the other: case report - Gebrim, Luiz Henrique; Bernardes Júnior, Júlio Roberto de Macedo; Nazário, Afonso Celso Pinto; Kemp, Cláudio; Lima, Geraldo Rodrigues de (São Paulo Medical Journal, 2000)
CONTEXT: The malignant variety of the phyllodes tumor is rare. The occurrence of invasive lobular carcinoma within fibroadenoma is rare as well. DESIGN: Case report. CASE REPORT: A 58-year-old black female patient was referred to the Mastology unit of the Department of Gynecology, Federal University of São Paulo / Escola Paulista de Medicina, in February 1990, presenting an ulcerated tumor in the right breast with fast growth over the preceding six months. She was a virgin, with meno-pause at the age of 45 years and had not undergone hormone replacement treatment. The physical examination showed, in her right breast, an ulcerated tumor of 20 x 30 cm which was not adher-ent to the muscle level, multilobular and with fibroelastic consistency. The axillary lymph nodes were not palpable. The left breast showed a 2 x 3 cm painless, movable nodule, with well-defined edges, and fibroelastic consistency. We performed left-breast mammography, which showed several nodules with well-defined edges, the largest being 2 x 3 cm and exhibiting rough calcification and grouped microcalcifications within it. The patient underwent a frozen biopsy that showed a malignant variant of the phyllodes tumor in the right breast and fibroadenoma in the left one. After that, we performed a total mastectomy in the right breast and an excision biopsy in the left one. Paraffin study confirmed the frozen biopsy result from the right breast, yet we observed that in the interior of the fibroadenoma that was removed on the left, there was a focal area of invasive lobular carcinoma measuring 0.4 cm. The patient then underwent a modi-fied radical mastectomy with total axillary lymphadenectomy. None of the 21 dissected lymph nodes showed evidence of metastasis. In the follow-up, the patient evolved asymptomatically and with normal physical and laboratory examination results up to July 1997.